(3efXheI aj YOI afhfs - (3GdHjGVj , CMeO Hf MSf Hf SfGf GdOjf, ceGd GdOjf,J (B1098 (3g` s
(3ChdgG (B:s
(3bGd CMeO MGeOkG ai HOA bGd eKfi GdJSdje hGdQVhGf fGd s
(3BNQgG (B:s
(3GP Ydi fOH aVd GTJeGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B112 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B192s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG JdhjK s
Keywords: (3GdLZQGajG h GdHdOGfs